Effects of an active ankle exoskeleton on the walking biomechanics of healthy men - Nagaraja, Sridevi; Rubio, Jose E.; Tong, Junfei; Sundaramurthy, Aravind; Pant, Anup; Owen, Meredith K.; Samaan, Michael A.; Noehren, Brian; Reifman, Jaques (Frontiers in Bioengineering and Biotechnology, 2025)
Active lower-body exoskeleton devices can decrease the energy requirement of the human body by providing mechanical assistance to lower-body muscles. However, they also alter gait kinematics and kinetics, and it is not well understood whether such alterations are detrimental or beneficial to the human body. In this pilot study, we investigated the impact of walking with an ankle exoskeleton device on the biomechanics of men while carrying a heavy load. We collected computed tomography images and motion-capture data for five young, healthy men who walked 5 km (∼60 min) with a 22.7-kg load, with and without an active ankle exoskeleton (the ExoBoot EB60). We developed personalized musculoskeletal models and calculated the joint kinematics and kinetics for each participant under each walking condition. Without the ExoBoot, at 5 km compared to 0 km, on average, the peak trunk flexion angle increased by ∼35% and the stride length increased by ∼3.5%. In contrast, with the ExoBoot, the magnitude of the corresponding increases was smaller (∼16% and ∼2%, respectively). After the 5-km walk, compared to walking without the ExoBoot, its use considerably altered hip-related biomechanical parameters, e.g., it increased hip abduction angle by ∼17%, increased hip flexion moment by ∼3.5%, and decreased hip adduction moment by ∼19%. Finally, irrespective of distance, ExoBoot use significantly increased the stance duration and peak ankle plantarflexion angle (p < 0.001). Overall, the use of the ExoBoot induced beneficial alterations in stride length and trunk-, ankle-, and hip-related parameters for men walking with load carriage. The quantitative analysis provided by this pilot study should help guide future investigations and inform the development of standards for safe and effective use of emerging exoskeleton technologies.